Is there servant leadership and job satisfaction in education teachers during the Covid-19 pandemic? - Yersi-Luis Huamán-Romaní , Luis-Alberto Castillo-Patiño, Elizabeth Molina-Chircca, Alfonzo Castillo- Alarcón, Ramiro Juro-García5a; Melinda Quispe-Anchayhua (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present work was carried out to demonstrate whether or not there is server leadership with secondary school teachers and through this to know the perspective on job satisfaction that they have in their institution during the Covid-19 pandemic; teachers have the need to organize themselves to seek and improve the quality of education. The method used for the research is descriptive, correlational, cross-sectional and predictive. The sample was conducted through an online survey where 64 teachers participated randomly from the three existing educational institutions. The study of the data was carried out using factor analysis and measuring Cronbach's alpha to relate the research variables. The results showed that, if there is servant leadership in the teachers in their respective institutions, implying that in spite of not knowing the concept of servant leadership, it is already being practiced in the educational institutions. With respect to the variable of job satisfaction, the teachers state that they are satisfied with their work in their educational institution despite the fact that they are not staying in their work center due to the current situation.